Expanding the frontiers of irrigation management research: Results of research and development at the International Irrigation Management Institute, 1984 to 1995 - Merrey, Douglas J. (International Irrigation Management Institute, 1997)
This volume reviews the findings and results of research of the International Irrigation Management Institute during its first decade. The book also reviews several of the institute?s major institutional strengthening activities.